TISH OG‘RIG‘INING SABABLARI VA UY SHAROITIDA BIRINCHI YORDAM (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article provides information on common causes of toothache — caries, pulpitis, periodontitis, tooth injury, and oral infections. It also focuses on first aid methods used at home to reduce tooth pain, including painkillers, traditional remedies, compresses, and proper hygiene practices. The article also addresses preventive measures to avoid toothache. Written based on medical literature, this article aims to enhance knowledge in the field of dentistry.